A first-in-class inhibitor of homologous recombination DNA repair counteracts tumour growth, metastasis and therapeutic resistance in pancreatic cancer - Calheiros, Juliana (2025)
The online version contains supplementary material available at: https://doi.org/10.1038/s41467-022-32178-3